Scaffold-free Scleraxis-programmed tendon progenitors aid in significantly enhanced repair of full-size Achilles tendon rupture. (May 2016) - Hsieh, Chi-Fen; Alberton, Paolo; Loffredo-Verde, Eva; Volkmer, Elias; Pietschmann, Matthias; Müller, Peter; Schieker, Matthias; Docheva, Denitsa
Aim: Currently there is no effective approach to enhance tendon repair, hence we aimed to identify a suitable cell source for tendon engineering utilizing an established clinically relevant animal model for tendon injury.Materials & methods: We compared, by in-depth histomorphometric evaluation, the regenerative potential of uncommitted human mesenchymal stem cells (hMSC) and Scleraxis ( Scx )-programmed tendon progenitors (hMSC-Scx) in the healing of a full-size of rat Achilles tendon defect.Results: Our analyses clearly demonstrated that implantation of hMSC-Scx, in contrast to hMSC and empty defect, results in smaller diameters, negligible ectopic calcification and advanced cellular organization and matrix maturation in the injured tendons.Conclusion : Scaffold-free delivery of hMSC-Scx aids in enhanced repair in a clinically translatable Achilles tendon injury model.